Assessing ICT Integration in Teaching Training: A Study of Moral Education Teacher Trainers at Universiti Pendidikan Sultan Idris, Malaysia - Salleh, Sakinah; Francis, Helda (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Communication and Information Technology (ICT ) has become a necessity in the education system. However, there are still teachers who have not integrated ICT into their teaching and learning. This research was carried out to examine the level of willingness to use ICT during teaching training among Moral Education teacher trainers at Universiti Pendidikan Sultan Idris (UPSI), Malaysia. The willingness aspect studied is knowledge, attitudes and practice. This study involved 103 teacher trainers as respondents. Study data was obtained from a set of research questions and analyzed using SPSS Version 25 software to obtain frequency, percentage and minimum. The results of the study show that the overall minimum score for the challenge of using ICT is high, while the differences in the level of knowledge readiness and attitudes towards the use of ICT during Teaching Training show that there is no significant difference between junior trainer teachers and senior trainer teachers. The implications of this study can help teacher trainers in integrating ICT in their teaching and learning.